Evaluation of the Factors Preventing the Opening of Health Facilities by SWARA Method - Kevser ŞAHİN; Büşra SEVİM; Yeter DEMİR USLU; Selenay KOÇ; Sefer AYGÜN (Bezmiâlem Science, 2025)
Objective: This study aims to prioritize the critical factors preventing the operation of healthcare facilities in Türkiye using the Step-Wise Weight Assessment Ratio Analysis (SWARA) method. Issues such as infrastructure, supply, geographical location, procurement processes, medical equipment supply, licensing and legal procedures, financial and human resource challenges encountered from the construction phase to service delivery are examined. Methods: The SWARA method was used to identify and prioritize the factors hindering healthcare facilities’ service delivery based on expert opinions, ranking these factors according to their importance. A total of eight criteria, derived from a comprehensive literature review, were assessed by five experts with relevant experience. The experts evaluated and ranked these factors, and the final prioritization was determined by calculating the geometric mean of their assessments. Results: According to the analysis, financial issues were found to be the most significant factor affecting the service delivery process, with a weight of 29%. This was followed by licensing and legal procedures at 19%, material supply issues at 14%, and infrastructure problems at 12%. Human resource issues were identified as the least important factor, with a weight of 3%. Conclusion: In line with the results obtained, stakeholders involved in the opening process have the opportunity to focus on and eliminate the problems related to them. At the same time, it also provides critical information about where those who plan the process should concentrate on inspections. In this way, health facilities will be able to start service provision at any time within the plan.